Combination of Gmelina arborea and Falcataria moluccana Extracts in Reducing Glucose and Improving Histology in Hyperglycemic Mice Model - Rumidatul, Alfi; Fadilah, Tyas I.; Rahayu, Amalia; Mawangi, Neng W. L.; Sandy, Pracilia S.; Kodariah, Liah; Mayuri, Nindya S. (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The White Teak plant (G. arborea) and Sengon (F. moluccana) contain flavonoids that act as antioxidants and have the potential to lower blood sugar levels. This study aims to examine the effects of G. arborea and F. moluccana extracts with polar and non-polar (methanol and n-hexane) solvents on blood glucose levels as well as the histological condition of the pancreas and liver in mice. The extract was obtained through maceration, and its effectiveness was tested by measuring blood glucose levels and conducting histological analysis of the organs. Data were analyzed using SPSS. The research results show that extracts of G. arborea and F. moluccana lower blood glucose levels and improve the histology of the pancreas and liver in mice. Polar solvents (methanol) are more effective in lowering blood glucose levels, while non-polar solvents (n-hexane) have a greater impact on improving organ histology. In conclusion, the extracts of these two plants have a positive effect on the liver condition of hyperglycemic mice.